Retrieval of aerosol episode due to agriculture biomass burning in the east-central China - Mukai, Sonoyo; Nakata, Makiko; Yasumoto, Masayoshi; Sano, Itaru; Kokhanovsky, Alexander (Frontiers in Environmental Science, 2015)
Aerosol distributions in East Asia are complicated owing to both natural factors and human activities. The concentration of air pollutants has become severe, and in recent years, influence of yellow sand and biomass burning aerosols generated by agricultural biomass burning (ABB) has been noted upon the severe haze episodes. This work intends to make the retrieval algorithm more efficient and to make the aerosol model more tractable as far as heavy air pollution caused by ABB is concerned. Aerosol retrieval in the hazy atmosphere is achieved based on radiation simulation method of successive order of scattering (MSOS) for the moderate resolution imaging spectroradiometer (MODIS) on AQUA data. The retrieved aerosol properties agree well with the ground measurements and numerical model simulations. Multi-angle observations with the polarization and directionality of the Earth's reflectances (POLDER) on the polarization & anisotropy of reflectances for atmospheric sciences coupled with observations from a lidar (PARASOL) are available for aerosol retrieval from a mixture of cloud and haze, and many potential applications of MSOS involving polarization information are expected to be available for cloud as well as aerosol episode. This study should draw our attention to the retrieval of aerosol/cloud from a variety of perspectives.